2015
DOI: 10.4269/ajtmh.15-0322
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Composition in Young Nicaraguan Children During Diarrhea Episodes and Recovery

Abstract: Abstract. Understanding how the gut microbiota is affected by diarrhea episodes may help explain alterations in intestinal function among children in low-income settings. This study examined the composition of the gut microbiome of Nicaraguan children both during diarrhea episodes and while free of diarrhea for at least 2 months. Relative abundances of bacterial taxa, phylogenetic diversity, and species richness were determined by 16S amplicon sequencing and compared between paired diarrhea and recovery sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…The decreased alpha diversity in HHGM pigs after VirHRV challenge was expected. A study evaluating microbiome and diarrhea found that diarrhea was associated with decreased phylogenetic diversity [25]. Although no samples were available for time points after PCD7, it is expected, given our data on enteropathy biomarkers, that diversity of HHGM pigs would return to normal levels.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The decreased alpha diversity in HHGM pigs after VirHRV challenge was expected. A study evaluating microbiome and diarrhea found that diarrhea was associated with decreased phylogenetic diversity [25]. Although no samples were available for time points after PCD7, it is expected, given our data on enteropathy biomarkers, that diversity of HHGM pigs would return to normal levels.…”
Section: Discussionmentioning
confidence: 89%
“…The samples were snap frozen in liquid nitrogen in the field, immediately transferred to −80 °C, shipped on dry ice to our lab, and stored at −80 °C until assayed. All stool samples underwent 16S rRNA amplicon sequencing for characterization of the gut microbiome, as previously described [25]. ELISAs for 4 biomarkers of enteropathy (α−1 antitrypsin, neopterin, myeloperoxidase and calprotectin) were run on the samples [38, 39].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among children, studies have considered the relationship between a diarrhea episode, which, in some cases, was associated with an enteric pathogen infection, and changes in the gut microbiota (Becker‐Dreps et al, ; Pop et al, ; Solano‐Aguilar et al, ; Subramanian et al, ; The et al, ). For example, in a large study of West African children, Pop et al () found the gut microbiota of those with moderate‐severe diarrhea to be less diverse than that of diarrhea‐free controls.…”
Section: Introductionmentioning
confidence: 99%